Essential Oil Composition of Pinus peuce Griseb. Needles and Twigs from Two National Parks of Kosovo. (8th August 2016) - Hajdari, Avni; Mustafa, Behxhet; Nebija, Dashnor; Selimi, Hyrmete; Veselaj, Zeqir; Breznica, Pranvera; Quave, Cassandra Leah; Novak, Johannes
Abstract : The principal aim of this study was to analyze the chemical composition and qualitative and quantitative variability of essential oils obtained from seven naturally grown populations of the Pinus peuce Grisebach, Pinaceae in Kosovo. Plant materials were collected from three populations in the Sharri National Park and from four other populations in the Bjeshkët e Nemuna National Park, in Kosovo. Essential oils were obtained by steam distillation and analyzed by GC-FID (Gas Chromatography-Flame Ionization Detection) and GC-MS (Gas Chromatography-Mass Spectrometry). The results showed that the yield of essential oils ( v/w dry weight) varied depending on the origin of population and the plant organs and ranged from 0.7 to 3.3%. In total, 51 compounds were identified. The main compounds were α -pinene (needles: 21.6–34.9%; twigs: 11.0–24%), β -phellandrene (needles: 4.1–27.7; twigs: 29.0–49.8%), and β -pinene (needles: 10.0–16.1; twigs: 6.9–20.7%). HCA (Hierarchical Cluster Analysis) and PCA (Principal Component Analyses) were used to assess geographical variations in essential oil composition. Statistical analysis showed that the analyzed populations are grouped in three main clusters which seem to reflect microclimatic conditions on the chemical composition of the essential oils.